Pengembangan Desa Wisata Kandri Berbasis Masyarakat - Anindya Kusuma Putri; Mardwi Rahdriawan (Teknik PWK (Perencanaan Wilayah Kota), 2016)
Until 2015, tourism sector in Indonesia always in the top five of the highest contributor to Indonesia’s foreign exchange. Government of Indonesia pays more attention to develop community based tourism in many villages since have a lot of potential natural resources and social culture. Kandri village is one of it in Semarang City. The existing of Kreo Cave and Jatibarang reservoir become the center of it that support the development of Kandri Village. The community should have awareness and enough knowledge to their village in order to develop community based tourism in Kandri. This research will analize the community readiness and define community readiness development strategy. Mix metode was used in this research. Qualitative metode was used to approach the community and explore the best-case practice of community based tourism in Gunungkidul develop the strategy for community base tourism in Kandri. Quantitative metode was used to measure the readiness level of the community.